The relationship between the functional status of upper extremity motor neurons and motor function and prognosis in stroke patients - Li, Xiaoyi; Shao, Zhen; Li, Zhi; Wei, Xiupan; Zong, Lijuan; Wang, Pei; Zhou, Ting; Wang, Hongxing (Frontiers in Neurology, 2024)
Introduction This study investigates the correlation between neuroelectrop-hysiological assessments such as motor unit number estimation (MUNE) and F-waves with upper extremity motor function and one-year prognosis in stroke patients. Methods Neuroelectrophysiological assessments of the abductor pollicis brevis muscle, including MUNE and F-waves, were conducted. Upper extremity motor function was evaluated using the Fugl-Meyer Assessment of Upper Extremity (FMA-UE) and the Modified Ashworth Scale (MAS). Pearson correlation and multiple linear regression analyses were performed to explore the relationship between upper extremity motor function and variables such as MUNE and F-waves. ROC curve analysis assessed the predictive ability of MUNE and F-waves for upper extremity motor function, and binary logistic regression analysis examined factors related to motor function improvement 1 year post-discharge. Results A total of 130 patients were ultimately included. Significant differences in MUNE and occupancy rate of non-repeater F-waves (non-ORF) were found between hemiplegic and unaffected sides (p < 0.001), with a significant difference in F-wave mean latency (p < 0.05). Pearson correlation analysis showed a positive correlation between FMA-UE at admission and hemiplegic side’s MUNE and non-ORF (p < 0.001). Multiple linear regression indicated that hemiplegic side’s MUNE (β = 0.88, p < 0.001) and non-ORF (β = 0.275, p = 0.005) influenced FMA-UE. ROC analysis demonstrated higher predictive ability for hemiplegic side’s MUNE (AUC = 0.696, p < 0.001) than non-ORF (AUC = 0.622, p = 0.018). Binary logistic regression showed that hemiplegic side’s MUNE was associated with FMA-UE improvement 1 year post-discharge. Conclusion MUNE and F-waves are correlated with upper extremity motor function in patients, reflecting their motor function status. These indicators have good predictive value for motor function and are associated with the prognosis of upper extremity motor function to a certain extent.